Insulated Cu wire free air ball characterization - Leong H.; Yap B.; Khan N.; Ibrahim M.R.; Tan L.C. (Elsevier Ltd, 2023)
Insulated Cu wire technology has immense potential for fine pitch wire bonding interconnection. Understanding the behavior of the insulated Cu free air ball (FAB) formation is crucial for wire bonding process. The FAB formation, size, shape and cleanliness under different conditions for 20 ?m insulated Cu wire were investigated using SEM, FESEM and FTIR surface analysis. The results were compared with that of bare Cu wire. Consistently spherical residue free FAB of insulated Cu wire were formed using forming gas. The samples with insulated Cu wire consistently produced larger FAB than that of bare Cu wire, indicating that the energy required for free air ball formation is lower. Basic bonding performances in terms of ball bond strength, intermetallic (IMC) coverage growth and stitch bond strength of insulated Cu wire at time zero are also discussed in the paper. © 2014 Elsevier Ltd. All rights.